THE TEACHERS' CLINIC. - Yankee, Glen G.; Woods, Richard S.; Boyd, F. Virgil; Perry, Kenneth W.; Downing, Glenn D.; Watson, Robert H. (The Accounting Review, 1960)
Abstract Fundamental income tax concepts should be taught in the elementary accounting course. The important reasons for this contention are: (1) Students are interested in the subject of income tax, and they have a need for tax knowledge. (2) Some accounting topics are taught better through the comparison of income tax and conventional accounting treatment. (3) A benefit may accrue to the teaching of the income tax accounting courses since accounting students will bring a better grounding in tax fundamentals to the course. Greater depth of treatment may be possible than is presently the case in courses in income tax accounting. (4) Students majoring in business education will be better prepared for their teaching duties.